2010
DOI: 10.1073/pnas.0914287107
|View full text |Cite
|
Sign up to set email alerts
|

Facilitation of murine cardiac L-type Ca v 1.2 channel is modulated by Calmodulin kinase II–dependent phosphorylation of S1512 and S1570

Abstract: Activity-dependent means of altering calcium (Ca 2+ ) influx are assumed to be of great physiological consequence, although definitive tests of this assumption have only begun to emerge. Facilitation and inactivation offer two opposing, activity-dependent means of altering Ca 2+ influx via cardiac Ca v 1.2 calcium channels. Voltage-and frequency-dependent facilitation of Ca v 1.2 has been reported to depend on Calmodulin (CaM) and/or the activity of Calmodulin kinase II (CaMKII). Several sites within the cardi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
67
1
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 73 publications
(70 citation statements)
references
References 53 publications
1
67
1
1
Order By: Relevance
“…inant role for phosphorylation of two other sites in the proximal C-terminal domain of Ca V 1.2 channels by CaMKII in voltagedependent facilitation of cardiac calcium currents in transfected cells and in murine heart in vivo (46,47). In light of those results, phosphorylation of Ca V 1.2-S1700 may be primarily involved in PKA regulation in response to activation of the sympathetic nervous system and β-adrenergic signaling.…”
Section: Resultsmentioning
confidence: 96%
“…inant role for phosphorylation of two other sites in the proximal C-terminal domain of Ca V 1.2 channels by CaMKII in voltagedependent facilitation of cardiac calcium currents in transfected cells and in murine heart in vivo (46,47). In light of those results, phosphorylation of Ca V 1.2-S1700 may be primarily involved in PKA regulation in response to activation of the sympathetic nervous system and β-adrenergic signaling.…”
Section: Resultsmentioning
confidence: 96%
“…Recently, we reported that CDF requires phosphorylation of Ca v 1.2 at Ser 1512/1570 (27). In contrast, Colbran and co-workers (22) reported that phosphorylation of Ca v ␤ 2 by CaMKII at Thr 500 modulated CDF.…”
Section: Resultsmentioning
confidence: 99%
“…27, 30, 31. Facilitation of I Ca was measured during a triple pulse protocol with a 200-ms control pulse to 0 mV (V1) followed by a 200-ms prepulse (V pre ) to ϩ80 mV followed by 200-ms test pulse to 0 mV (V2) (27). The extent of voltage-dependent facilitation was calculated as the ratio of the peak current during V2 and V1.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A growing body of evidence has demonstrated that CaMKII can also be activated by ROS 21, 22, 23, 24. Once activated, CaMKII can phosphorylate a wide range of key Ca 2+ and Na + regulatory proteins such as LCCs,25, 26, 27, 28 RyRs,29, 30, 31, 32, 33, 34, 35 phosphalamban,29, 34, 36 and Na + channels 37, 38. Importantly, Xie et al39 showed that H 2 O 2 perfusion–induced oxidative CaMKII activation leads to afterdepolarizations in isolated rabbit cardiomyocytes, likely by phosphorylation of Na + channels and LCCs.…”
Section: Introductionmentioning
confidence: 99%